Case Report: Endoscopic resection of giant colonic pedunculated polyps in patients with AIDS using a novel nylon rope and titanium clip technique - Xie, YongXiang; Zheng, YongLi; Tang, Qian; Wang, DongMei (Frontiers in Oncology, 2025)
The three patients with AIDS were all male, aged between 56 and 67 years. One also had liver cirrhosis. They presented to the Chengdu Public Health Clinical Medical Center with a history of several months of blood in the stool. Colonoscopy revealed large pedunculated polyps in the sigmoid colon, with the largest measuring 5 cm and the smallest 3.5 cm. The polyps nearly completely obstructed the lumen. The long, thick stems were freely mobile within the narrow lumen, making it difficult to capture sufficient tissue with the inner ring of the forceps. The entire colon was examined with the aid of a transparent cap. Once the polyp was located, fecal water and residue surrounding it were removed. The polyp surface was then examined using white light and narrow-spectrum light to assess its structure. A biopsy was performed when cancer was suspected. During the procedure, we innovatively used a Harmony Clamp (ROCC-D-26-195; Micro Tech, Nanjing, China) to assist the nylon rope (HX-400U-30; Olympus, Tokyo, Japan) in pre-treating the pedicle root. First, the nylon rope was preloaded into the forceps channel of the enteroscope (EC-550L; SonoScape, Shenzhen, China), and the pedicle was ligated. When the polyp head turned deep purple and the stalk became pale, it confirmed that the blood supply to the mass had been fully blocked. A Harmony Clamp was then inserted into the intestinal cavity through the forceps channel, and the nylon rope was secured around the base of the polyp. The electric snare (VDK-SD-23-230-25-A1; Vedkang, Jiangsu, China) was placed between the clamp and the polyp, at least 0.5 cm from the mass, followed by high-frequency electroresection. Postoperatively, the wound appeared white with no bleeding or perforation. The operation time for all three patients was between 5 and 7 minutes, and there were no complications such as bleeding, perforation, or abdominal pain during or after the procedure. Follow-up colonoscopy 1 to 3 months later showed scar formation in the surgical area and no recurrence. Pathological analysis revealed that two cases were tubular-villous adenomas, and one case was a tubular-villous adenoma with focal high-grade intraepithelial neoplasia and mucosal carcinoma, with negative horizontal and vertical margins.